2014
DOI: 10.1128/aem.00261-14
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Effect of the Different N-Glycosylation Sites on the Secretion, Activity, and Stability of Cellobiohydrolase I from Trichoderma reesei

Abstract: N-linked glycosylation modulates and diversifies the structures and functions of the eukaryotic proteome through both intrinsic and extrinsic effects on proteins. We investigated the significance of the three N-linked glycans on the catalytic domain of cellobiohydrolase I (CBH1) from the filamentous fungus Trichoderma reesei in its secretion and activity. While the removal of one or two N-glycosylation sites hardly affected the extracellular secretion of CBH1, eliminating all of the glycosylation sites did ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 53 publications
4
22
0
Order By: Relevance
“…Szengyel and Zacchi [27] showed that acetic acid had no inhibition effect on Trichoderma reesei cellulase activities, but increasing acetic acid concentrations improved BGL1 activity. Similar results on cellulases were reported by Qi et al [28], except that acetic acid had an inhibitory effect on BGL1. Formic acid is also known as a potent inhibitor of hydrolysis and has been shown to decrease glucose production, while increasing concentration of furfural inhibited both cellulase and BGL1 activities [29].…”
Section: Introductionsupporting
confidence: 86%
“…Szengyel and Zacchi [27] showed that acetic acid had no inhibition effect on Trichoderma reesei cellulase activities, but increasing acetic acid concentrations improved BGL1 activity. Similar results on cellulases were reported by Qi et al [28], except that acetic acid had an inhibitory effect on BGL1. Formic acid is also known as a potent inhibitor of hydrolysis and has been shown to decrease glucose production, while increasing concentration of furfural inhibited both cellulase and BGL1 activities [29].…”
Section: Introductionsupporting
confidence: 86%
“…6). Similarly, previous work revealed that in Trichoderma reesei, abolishing N-glycosylation of CBH1 led to the induction UPR target gene expression, with 5-, 4-, and 2-fold up-regulation of CNE1, BIP1, and PDI1, respectively (72). These results thus demonstrated that elimination of glycosylation sites can lead to a range of different effects on the folding and stabilization of glycoproteins in oomycetes, though further exploration is needed to characterize the full extent and underlying mechanisms of these effects.…”
Section: Most Of the 496 N-glycosylation Sites Matched With The Consesupporting
confidence: 57%
“…His tag fusion proteins were then expressed in E. coli BL21(DE3). The crude enzyme solutions were purified using a fast protein liquid chromatography system consisting of nickel-nitrilotriacetic acid (Ni-NTA) and DEAE columns (33).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, N-glycosylation represents a stabilizing factor against proteolytic cleavage by proteases (29). Apart from conferring an increased resistance to proteolysis, N-glycosylation can also enhance enzyme thermostability and alter catalytic activity (30)(31)(32)(33). The improved conformational stability of enzymes derived from the steric interactions between N-linked glycan and protein can decrease the enzyme flexibility or increase the rigidity of the enzyme structure (34,35).…”
mentioning
confidence: 99%